Betwixt and between: Chiefs and reform of Sierra Leone's justice sector - Peter Albrecht (Danish Institute for International Studies (DIIS), 2010)
This paper discusses the uneasy role of chiefs within three cycles of security and justice reform in Sierra Leone during the past decade. Interaction has been indirect, by default or marginal, and always hesitant. This has been the case, even though chiefs constitute the most important governing institution in Sierra Leone's rural communities. One of the key tensions, I argue, has been the tendency to cast chiefs as state or non-state, respectively, or even as a hybrid between the two. However, as illustrated in this paper, while they are formally and discursively tied into a 'state system' in the Constitution and in legislation, they are subjected to limited oversight, and therefore govern in relative autonomy. A new program, designed in 2010, might help to transcend the state-non-state dichotomy and prepare the ground for a more productive way of engaging chiefs that do not fit into either a state or non-state category. This is done by focusing on which actors are actually providing security and justice, rather than who donors would prefer did it, i.e., the state.
Keywords: 330